Chromosome aberrations and DNA damage in petrol pump workers in Chiang Mai - Moohammadaree, Aida; Puaninta, Chaniporn; Mevatee, Umnat (Biomedical Sciences and Clinical Medicine, 2024)
Objective The objective of this study was to investigate the genetic damage in petrol pump workers, who were exposed occupationally to gasoline, its derivatives, and air pollution through inhalation and skin contamination, and to compare them with control subjects. Methods The chromosome aberration test and single cell gel electrophoresis (comet assay) were used to evaluate the DNA status in peripheral blood lymphocytes of 32 petrol pump workers from eight different gasoline stations in central Chiang Mai, Thailand. Thirty control subjects, who had not been exposed occupationally to benzene, were matched to the exposed subjects by gender and age. Results The comet assay revealed that DNA damage in the peripheral blood lymphocytes of petrol pump workers was significantly higher than that in the controls. The average tail length and tail moment in the exposed workers were 5.51±5.46 μm and 1.85±2.67 μm, respectively, based on 100 cells/individual, whereas, the average tail length and tail moment in the control group were 1.57±1.03 μm and 0.31±0.27 μm, respectively. In addition, results of the chromosome aberration test showed that the frequency of cell with aberrations in exposed workers was significantly higher than that of control subjects, 1.87% vs. 1.06%, respectively. Conclusion This study found a significant excess of DNA damage and structural chromosome aberrations in workers who were exposed occupationally to gasoline vapor and air pollutants, when compared to the matched controls. These fi ndingsconfi rm the potent genotoxic effect of gasoline and air pollutants as an inducer of DNA damage and structural chromosome aberrations.